Redescription of "Amaurobius" rufipes Taczanowski, 1874 (Araneae: Corinnidae) with notes of Amaurobius species described from French Guyana - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2015)
Amaurobius rufipes Taczanowski, 1874 was described on the basis of a syntype series consisting of two males, two females and some juveniles collected in Cayenne, French Guyana (Taczanowski 1874). Simon (1898) doubted this species belonged to Amaurobius and thought that it was related to the Corinna species group: "C'est probablement aussi au groupe des Corinna qu'appartiennent les espèces de la Guyane décrites par Taczanowski sous les noms d'Amaurobius cayanus, rufipes, brevis, et hirtus Tacz.". Lehtinen (1967), who possibly studied the types, transferred A. rufipes and other Amaurobius species described from Guyana by Taczanowski into Corinnidae, although new combinations were not suggested. In the World Spider Catalog (Platnick 2014), this species is listed as "Amaurobius" rufipes among Corinnidae as incertae sedis. It is likely that no-one has studied the types of Guyanese "Amaurobius", and Corinnidae from Guyana have never been revised or mentioned in taxonomic publications (e.g. Bonaldo 2000).